2020
DOI: 10.1111/aogs.14026
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic findings in normotensive women with small‐for‐gestational‐age and growth‐restricted fetuses

Abstract: Introduction Fetal growth restriction (FGR) in most instances is a consequence of primary placental dysfunction due to inadequate trophoblastic invasion. Maternal cardiac maladaptation to pregnancy has been proposed as a possible determinant of placental insufficiency and impaired fetal growth. This study aimed to compare the maternal hemodynamic parameters between normotensive women with small‐for‐gestational‐age (SGA) and FGR fetuses and to evaluate their correlation with neonatal outcome. Material and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Additionally, several studies also demonstrated differences in the hemodynamic profile of normotensive women with small‐for‐gestational age or FGR compared to uncomplicated pregnancies. In such context, fetal smallness was also associated with reduced CO and increased PVR were associated with fetal smallness, 6,11–20 which further supports the hypothesis of an inadequate maternal cardiovascular adaptation to the pregnancy as a determinant of placental dysfunction.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Additionally, several studies also demonstrated differences in the hemodynamic profile of normotensive women with small‐for‐gestational age or FGR compared to uncomplicated pregnancies. In such context, fetal smallness was also associated with reduced CO and increased PVR were associated with fetal smallness, 6,11–20 which further supports the hypothesis of an inadequate maternal cardiovascular adaptation to the pregnancy as a determinant of placental dysfunction.…”
Section: Introductionsupporting
confidence: 67%
“…More specifically, FGR was shown to be associated with lower CO and higher PVR compared to SGA, furthermore the hemodynamic profile was shown to be similar in mothers diagnosed with a SGA fetus and uncomplicated pregnancies. 11,13,20 Furthermore, the reduced CO recorded in FGR compared to SGA was shown to be determined by a reduction in the HR but not in the SV. 20 A summary of the maternal hemodynamics changes occurring during normal pregnancy and in placenta-related pathologies is shown in Figure 1.…”
Section: The Characteristics Of Maternal Haemodinamics In Pre-eclamps...mentioning
confidence: 85%
“…The nature of this pathophysiologic pathway is in line with the reported increased serum concentrations of atrial natriuretic peptide ( 52 ) and copeptin/vasopressin in PE ( 53 ) and with the impaired expansion of maternal plasma volume in EPE ( 9 ). The early gestational onset of this phenomenon is also supported by the shallow, but significant, rise of serum hemoglobin concentrations and hematocrit in the first trimester of pregnancies destined to develop EPE ( 31 , 54 , 55 ) but not in those eventually leading to FGR ( 56 ). As explained above and illustrated in Figure 1 , FGR pregnancies show a normal rise of plasma volume and total body water, superimposed upon constitutionally low body water already present before conception.…”
Section: Pathways Of Maternal Low Volume Circulation In Early Onset P...mentioning
confidence: 89%
“…This observation has also been reported by others ( 29 ) and linked to a condition of low CO that is already present before conception ( 17 ). Low CO in FGR pregnancies mainly results from low SV ( 30 , 31 ) and to a lesser degree from low HR ( 32 , 33 ). Throughout an uncomplicated pregnancy, the fraction of CO deviated to the uterus doubles from 6 to 12% ( 34 ) and is achieved by an increase of (distal) internal iliac artery impedance in concert with a reduction of uterine artery impedance ( 35 ).…”
Section: Maternal Hemodynamics and Fetal Growthmentioning
confidence: 99%
“…Increased peripheral vascular resistance in mothers with chronic hypertension is highly predictive of birthweight and FGR by mid-pregnancy (Vasapollo et al, 2022), and lower cardiac output and increased systemic resistance was observed with FGR. These parameters were also a strong indicator of subsequent neonatal hospitalization (Di Pasquo et al, 2021). Reduced maternal perfusion can lead to lesions related to hypoxia.…”
Section: Plasma and Maternal Cardiovascular And Serum Biomarkersmentioning
confidence: 96%